Mediating Islam and Modernity - Owais Manzoor Dar (International Institute of Islamic Thought, 2019)
The question of Islam’s compatibility with modernity (and other interrelated aspects like democracy, rationality, nationalism, etc.) has been debated for more than two centuries. In the Subcontinent, this debate started with British imperialism (the so-called British Raj, 1857-1947). Scholars like Chirag Ali (d. 1895), Sir Syed Ahmad Khan (d. 1898), Allama Iqbal (d. 1938), Abul Kalam Azad (d. 1958), Shibli Numani (d. 1914), Mumtaz Ali (d. 1974), Syed Mawdudi (d. 1979), Amin Ihsan Islahi (d. 1997), and Abul Hassan Ali Nadwi (d. 1999) offered various critical responses. The debate still manifests in different forms, whether regarding nationalism or secularism, rationality or progressive politics. A plethora of mostly apologetic literature has been produced on the question. A recent addition to this literature is Parray’s Mediating Islam and Modernity.